2023
DOI: 10.3390/ma16062512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Treatment Time on Microstructure Evolution and Properties of Mg-3Y-4Nd-2Al Alloy

Abstract: In order to explore the microstructure evolution of an Mg-RE alloy refined by Al during solution treatment, an Mg-3Y-4Nd-2Al alloy was treated at 545 °C for different time periods. Phase evolution of the alloy was investigated. After solution treatment, the Mg-RE eutectic phase in the Mg-3Y-4Nd-2Al alloy dissolves, the granular Al2RE phase does not change, the acicular Al11RE3 phase breaks into the short rod-like Al2RE phase, and the lamellar Al2RE phase precipitates in the grains. With the extension of soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To address this issue, considerable attention has been directed towards enhancing the mechanical properties of Mg alloys [4][5][6][7][8]. Research has shown that incorporating rare earth (RE) elements through alloying is a viable approach to strengthen Mg alloys [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, considerable attention has been directed towards enhancing the mechanical properties of Mg alloys [4][5][6][7][8]. Research has shown that incorporating rare earth (RE) elements through alloying is a viable approach to strengthen Mg alloys [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by alloying with double RE elements, Y and Nd, properly instead of Gd, an ultra-high UTS of 293 MPa was achieved in a Mg-8Gd-2Nd-1Y alloy after peak-aging treatment [17]. The decrease in the total amount of RE is due to the fact that the addition of multiple RE elements can reduce their solubility in Mg, thereby forming a supersaturated solid solution with less RE content [7,10]. Inspired by this idea, we designed a multiple RE-strengthened, Mg-2Gd-2Y-2Nd-2Sm-based Mg-RE alloy to obtain prismatic precipitates with less RE (8 wt.%) and thereby reduce the density as well as the cost of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…However, their absolute strength and creep resistance are low, hence their application scopes are still far from those of steel and aluminum alloys. Rare Earth (RE) elements are very effective strengthening elements for Mg alloys, such as Y, Nd, Sm, Gd, and Dy [6][7][8]. They act as obstacles for dislocation movement as solute atoms and can also be used for grain boundary pinning in the form of intermetallic phases.…”
Section: Introductionmentioning
confidence: 99%